The EcoGothic in Margaret Atwood’s Oryx and Crake and The Year of The Flood - Tan, Si Hui (2017)
Fear of mortality is often a key anxiety within dystopian contexts and located within Margaret Atwood’s MaddAdam trilogy, where a biological virus created by the scientist Crake has killed off most of humanity. In this essay, I examine the Eco-Gothic in Atwood’s presentation of genetic technology as a source of fear through a close reading of Oryx and Crake and The Year of The Flood and the hybrid creatures within the trilogy. By focusing on the Eco-Gothic as an approach to reading the monstrosity of the genetic technology used in the transhuman dystopia of Atwood’s trilogy, the transhuman anxieties of the fear of mortality thus appears to be a manifestation of the various ecological anxieties. This essay argues that the post-human environment of the aftermath of the environmental apocalypse creates a new humanity, one that requires a new conception of mortality which rejects an anthropocentric hierarchical position in considering humanity’s approach to the physical environment. This essay also argues that Atwood’s trilogy presents the Gothic construction of body as a source of ecological anxieties. In doing so, this essay conveys not just the necessity of being concerned with the protection of the physical environment on the basis of self-interest because of a fear of human mortality, but also a growing ecological consciousness that advocates a non-anthropocentric restoration of the physical environment.